1984
DOI: 10.1002/bms.1200111004
|View full text |Cite
|
Sign up to set email alerts
|

Application of fast atom bombardment mass spectrometry to biological samples: Analysis of urinary metabolites of acetaminophen

Abstract: Fast atom bombardment (FAB) is useful for the characterization of all major metabolites of the analgesic acetaminophen (APAP). It is particularly useful for providing mass spectra of the polar glucuronide and sulfate conjugates which eluded identification by field desorption and other more conventional methods of ionization. A protocol is described for the use of FAB in the identification of urinary APAP metabolites isolated by reversed phase high-performance liquid chromatography (HPLC) following therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1985
1985
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Strong ion currents are temporally prolonged under the high-flux primary beams used in FAB only if the matrix is fluid.56,110 Several investigators report obtaining better spectra by heating viscous matrices or samples.58,111-113 One interesting heated matrix is the saturated glucose solution (syrup) suggested by Watson and co-workers for carbohydrate analysis. 113 Spectra contain less matrix-contributed background; however, ion lifetimes appear not to be as long as those provided by a glycerol system well matched to the sample.…”
Section: B Fluiditymentioning
confidence: 95%
See 1 more Smart Citation
“…Strong ion currents are temporally prolonged under the high-flux primary beams used in FAB only if the matrix is fluid.56,110 Several investigators report obtaining better spectra by heating viscous matrices or samples.58,111-113 One interesting heated matrix is the saturated glucose solution (syrup) suggested by Watson and co-workers for carbohydrate analysis. 113 Spectra contain less matrix-contributed background; however, ion lifetimes appear not to be as long as those provided by a glycerol system well matched to the sample.…”
Section: B Fluiditymentioning
confidence: 95%
“…A sample with surfactant properties usually suppresses matrix ions of this kind, depending on its concentration. Consequently, it is not always easy to obtain an appropriate matrix spectrum for background subtrac-tion98, 129 The presence of alkali metal salts, e.g., sodium chloride, in the matrix further confound the pattern of ions contributed by the matrix, since these may also include clusters with metal ions. Matrix molecules may also form cluster ions with sample molecules, e.g., sample + H+ + matrix, usually accompanying protonated or natriated molecules at the expected mass increment.…”
Section: Chemical Background and Noisementioning
confidence: 99%
“…Earlier studies demonstrated the utility of fast atom bombardment mass spectrometry (FAB/MS) for identification of specific thioether conjuAddress reprint requests to Dr. A. Daniel Jones, Facility for Adv anced Instrumen tation, University of California, Dav is, CA 95616. E-mail: adjones@ucdavis.edu gates from biological samples [3,4,[13][14][15][16][17] . Using FAB or newer ionization techniques coupled with tandem mass spectrometry (MS/MS), researchers determined structures of thioether conjugates extracted from biological matrices [3][4][5][6][7][8][13][14][15][16][17][18][19][20][21][22].…”
mentioning
confidence: 99%
“…Experiments were carried out on a modified Varían MAT CH5 double focusing mass spectrometer equipped with an Ion Tech FAB gun (Teddington, UK). Details of the instrument configuration have been published previously (3). Ultra-high-purity xenon was used to generate a beam of fast atoms (8 kV) in all experiments.…”
Section: Methodsmentioning
confidence: 99%